Enrichment of anaerobic syngas-converting bacteria from thermophilic bioreactor sludge - Alves, J. I. (2013)
Thermophilic (55 °C) anaerobic microbial communities were enriched with a synthetic syngas mixture (composed of CO, H2, and CO2) or with CO alone. Cultures T-Syn and T-CO were incubated and successively transferred with syngas (16 transfers) or CO (9 transfers), respectively, with increasing CO partial pressures from 0.09 to 0.88 bar. Culture T-Syn, after 4 successive transfers with syngas, was also incubated with CO and subsequently transferred (9 transfers) with solely this substrate – cultures T-Syn-CO. Incubation with syngas and CO caused a rapid decrease in the microbial diversity of the anaerobic consortium. T-Syn and T-Syn-CO showed identical microbial composition and were dominated by Desulfotomaculum and Caloribacterium species. Incubation initiated with CO resulted in the enrichment of bacteria from the genera Thermincola and Thermoanaerobacter. Methane was detected in the first two to three transfers of T-Syn, but production ceased afterward. Acetate was the main product formed by T-Syn and T-Syn-CO. Enriched T-CO cultures showed a two-phase conversion, in which H2 was formed first and then converted to acetate. This research provides insight into how thermophilic anaerobic communities develop using syngas/CO as sole energy and carbon source can be steered for specific end products and subsequent microbial synthesis of chemicals.